Lipidomic Analysis Reveals Serum Alteration of Plasmalogens in Patients Infected With ZIKA Virus - Queiroz, Adriano; Pinto, Isabella Fernanda Dantas; Lima, Maricélia; Giovanetti, Marta; de Jesus, Jaqueline Goes; Xavier, Joilson; Barreto, Fernanda Khouri; Canuto, Gisele André Baptista; do Amaral, Helineide Ramos; de Filippis, Ana Maria Bispo; Mascarenhas, Denise Lima; Falcão, Melissa Barreto; et al. (Frontiers in Microbiology, 2019)
Zika virus (ZIKV) is an arthropod-borne virus (arbovirus) in the Flavivirus genus of the Flaviviridae family. Since the large outbreaks in French Polynesia in 2013 – 2014 and in Brazil in 2015, ZIKV has been considered a new public health threat. Similar to other related flavivirus, ZIKV is associated with mild and self-limiting symptoms such as rash, pruritus, prostration, headache, arthralgia, myalgia, conjunctivitis, lower back pain and, when present, a short-term low grade fever. In addition, ZIKV has been implicated in neurological complications such as neonatal microcephaly and Guillain–Barré syndrome in adults. Herein, serum lipidomic analysis was used to identify possible alterations in lipid metabolism triggered by ZIKV infection. Patients who presented the virus-like symptoms such as fever, arthralgia, headache, exanthema, myalgia and pruritus were selected as the control group. Our study reveals increased levels of several phosphatidylethanolamine lipid species in the serum of ZIKV patients, the majority of them plasmenyl-phosphatidylethanolamine (or plasmalogens) linked to polyunsaturated fatty acids. Constituting up to 20% of total phospholipids in humans, plasmalogens linked to polyunsaturated fatty acids are particularly enriched in neural membranes of the brain. The biosynthesis of plasmalogens requires functional peroxisomes, which are important sites for viral replication, including ZIKV. Thus, increased levels of plasmalogens in serum of ZIKV infected subjects suggest a link between ZIKV life cycle and peroxisomes. Our data provide important insights into specific host cellular lipids that are likely associated with ZIKV replication and may serve as platform for antiviral strategy against ZIKV.